Festival Kuliner Wedang Ereng- Ereng Dalam Rangka Mendukung Desa Wisata Seloharjo - Sutrisno, Sutrisno; Kamardiani, Diah Rina; Satyarini, Tr iwara Buddhi (Berdikari: Jurnal Inovasi dan Penerapan Ipteks, 2019)
Wedang Ereng-ereng Culinary Festival activity is held in order to support the mandate of Seloharjo village as atourism village. Based on three natural potentials, namely Goa Jepang, Tuk Surocolo, and Goa Sunan Mas, WedangEreng-ereng is expected to become a typical culinary attraction. This festival is intended as an internal and externalpromotion effort as well as to make Wedang Ereng-ereng as the tourism icon of Seloharjo. The festival activity iscarried out in four stages, namely: preparation, socialization, festival implementation, and follow-up plans. Thecommunity is involved in all stages as the main actors of Seloharjo tourism development. This festival has succeededin making people aware of the potential and opportunities of Wedang Ereng-ereng as a source of communityincome.